Determinan ketidakpatuhan terapi antiretroviral pada orang dengan HIV/AIDS dewasa - Zulpahmi Harahap; Eggi Arguni; Theodola Baning Rahayujati (Fakultas Kedokteran Universitas Gadjah Mada, 2016)
Determinants of non-adherence to antiretroviral therapy in adults with HIV/AIDSPurposeThis study aimed to determine the factors of non-adherence ARV therapy in adult PLWHA.MethodsA case-control study was conducted using secondary data of the Cilacap VCT clinic with consecutive sampling technique. The total sample was 204, consisting of 102 cases and 102 controls (1:1). The cases were adult PLWHA who did not adhere to ARV therapy and the controls were adult PLWHA who adhere to ARV therapy. The bivariate analysis used Chi-square and Fisher's exact tests and multivariate analysis used logistic regression tests. ResultsThe variables that were shown to jointly affect non-adherence to ARV therapy in adult PLWHA were the level of education, CD4 count, PMO and opportunistic infections.ConclusionsThe risk factors of non-adherence to ARV therapy in adult PLWHA were the level of education, PMO, CD4 count and opportunistic infections. There needs to be a special assistance and counseling program on a regular basis to PLWHA adults with low education, obligating all PLWHA adults that start ARV therapy to have a PMO, continue HIV screening programs to entire population at risk and advocate the local governments to facilitate PLWHA who can not afford to obtain CD4 test .